A Rare Case of Pleural Leiomyoma - (:unkn) unknown (My University, 2017)
Elli altı yaşında kadın hasta üç yıldır devam eden göğüs ağrısı, nefes darlığı ve göğsünün sağ tarafında şişlik yakınmaları ile başvurdu. Akciğer grafisinde ve bilgisayarlı toraks tomografisinde sağ akciğerde 16x13x12 cm ebadında kitle lezyonu görüldü. Hastaya sağ torakotomi uygulandı. Kitle mediastinal plevradan kaynaklanıyordu. Tümör parçalanarak çıkarıldı. Makroskopik olarak tümör sert, düzensiz yüzeyli, beyaz-sarı renkte bir kitle idi. Histolojik olarak olarak belirgin hücresel nekroz ve mitotik aktivitesi olmayan düz kas liflerinden oluşuyordu. Amacımız çok nadir görülen plevral kaynaklı leimiyomanın malignite potansiyelinden dolayı çıkarılması gerektiğini vurgulamaktır.

A 56-year-old female patient presented with chest pain and shortness of breath ongoing for 3 years. Chest X-ray and computed tomography of the thorax revealed mass 16 x 13 x 12 cm in size in the right middle and lower lobes. Right posterolateral thoracotomy was performed. According to frozen biopsy, mass was determined to be degenerative leiomyoma. Histopathologically, tumor consisted of packets and bundles of smooth muscle fibers without significant cellular necrosis or mitotic activity. Macroscopic appearance of the tumor was white-yellow color and texture was very hard. Due to size and location, tumor was removed with 2 incisions. Aim of this report was to emphasize the need for removal of leiomyoma due to malignant potential of pleural origin
Nadir Bir Plevral Leimiyoma Olgusu
Keywords: Solunum Sistemi